How stressful are economic competitions in the lab? An investigation with physiological measures - Magdalena Buckert; Christiane Schwieren; Brigitte M. Kudielka; Christian J. Fiebach (University of Heidelberg, Department of Economics, 2015)
Competition is ubiquitous in economic life. Yet, negative consequences of competitive environments have been reported and everyday experience suggests that competitive situations can be very stressful. It is, however, an open question whether or not economic competitions in the laboratory indeed elicit physiological stress reactions. Our study examined the subjectively perceived stress and the physiological changes induced by a well-established economic laboratory competition paradigm (first used in Niederle and Vesterlund 2007) in a mixed-gender sample of 105 healthy participants. A mental arithmetic task was performed first under a piece rate (i.e., non-competitive) payment scheme and afterwards under a tournament condition. In a third round, participants decided how to be paid (i.e., piece rate or tournament). Our results indicate that compared to a control group, which performed only the non-competitive condition, the competitive game condition indeed elicited subjective and physiological reactions that are indicative of mild stress. Furthermore, reactions that are thought to reflect an active coping style were related to the self-selection into competition in the third round of the game. We speculate that real-life economic competitions might be even stronger stressors and the way how people cope with this kind of stress might be related to competitiveness in real-life economic contexts.
urn:nbn:de:bsz:16-heidok-187487
Keywords: 330; competition; decision making; stress; heart rate; testosterone; economic tournament